2021
DOI: 10.1001/jama.2020.23523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endovascular Treatment Alone vs Intravenous Alteplase Plus Endovascular Treatment on Functional Independence in Patients With Acute Ischemic Stroke

Abstract: IMPORTANCEFor patients with large vessel occlusion strokes, it is unknown whether endovascular treatment alone compared with intravenous thrombolysis plus endovascular treatment (standard treatment) can achieve similar functional outcomes. OBJECTIVE To investigate whether endovascular thrombectomy alone is noninferior to intravenous alteplase followed by endovascular thrombectomy for achieving functional independence at 90 days among patients with large vessel occlusion stroke.DESIGN, SETTING, AND PARTICIPANTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
459
4
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 403 publications
(487 citation statements)
references
References 31 publications
18
459
4
6
Order By: Relevance
“…Moreover, some studies enrolled patients who were eligible for IVT into the direct EVT arm (17)(18)(19)(20), whereas others enrolled patients who were not eligible for IVT into direct EVT treatment (21)(22)(23)(24), which made these studies uncomparable. Recently, three RCTs have shown that bridging treatment was not superior to direct EVT for patients who were also eligible for IVT (25)(26)(27). Because of the controversies in this field regarding the application of bridging treatment (combining prior IVT and EVT) and direct EVT, a meta-analysis was needed to explore the advantages and disadvantages of both approaches of treatment in patients with IVT eligibility.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies enrolled patients who were eligible for IVT into the direct EVT arm (17)(18)(19)(20), whereas others enrolled patients who were not eligible for IVT into direct EVT treatment (21)(22)(23)(24), which made these studies uncomparable. Recently, three RCTs have shown that bridging treatment was not superior to direct EVT for patients who were also eligible for IVT (25)(26)(27). Because of the controversies in this field regarding the application of bridging treatment (combining prior IVT and EVT) and direct EVT, a meta-analysis was needed to explore the advantages and disadvantages of both approaches of treatment in patients with IVT eligibility.…”
Section: Introductionmentioning
confidence: 99%
“…The DEVT (Direct Endovascular Thrombectomy vs. Combined IVT and Endovascular Thrombectomy for Patients With Acute Large Vessel Occlusion in the Anterior Circulation) trial in China also demonstrated the non-inferiority of primary MTE treatment over the bridging therapy (standard-dose IVT + MTE) in functional independence (noninferiority margin of 10%) (8). However, there may be individual factors in the decision-making process that were not captured in the clinical trials (2).…”
Section: Introductionmentioning
confidence: 99%
“…The door-to-needle times of DIRECT-MT, 1 DEVT 2 and SKIP 3 were 59 (45-78) min, 61 (49-81) min and 50 min, respectively, which represent a substantial delay in relation to the 40 (29-55) min reported in the HERMES meta-analysis (Highly Effective Reperfusion Evaluated Open access in Multiple Endovascular Stroke Trials) and may have resulted in lower rates of favourable outcomes than what would have been accomplished with shorter door-toneedle times. 7 Moreover, the rates of favourable outcomes noted in DIRECT-MT 1 were significantly lower than those noted in DEVT 2 and SKIP. 3 This may be related to the differences of stroke aetiology across the trials with varying proportions of undetermined causes and intracranial atherosclerosis.…”
Section: Merits and Shortcomingsmentioning
confidence: 79%
“…1 Likewise, the recently published DEVT (Direct Endovascular Thrombectomy vs Combined IVT and Endovascular Thrombectomy for Patients With Acute Large Vessel Occlusion in the Anterior Circulation) trial involving 234 Chinese patients who had an anterior circulation LVOS found that the rate of functional independence (90-day mRS ≥2) in dEVT group was numerically higher than that in the BT group (54.3% vs 46.6%, difference: 7.7%, 1-sided 97.5% CI: −5.1% to ∞; p=0.003 for non-inferiority). 2 With prespecified noninferiority threshold of 10% for the favourable outcome proportion difference, the trial concluded that dEVT was non-inferior to BT. 2 Simultaneously published with DEVT, the SKIP (Direct Mechanical Thrombectomy in Acute LVO Stroke) trial included 204 patients who had an acute ischaemic stroke with internal carotid artery or middle cerebral artery M1 occlusions presenting within 4.5 hours of stroke onset across 23 sites in Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation